Crystal structures of spinel-type Na(2)MoO(4) and Na(2)WO(4) revisited using neutron powder diffraction - Fortes, A. Dominic (Acta Crystallogr E Crystallogr Commun, 2015)
Time-of-flight neutron powder diffraction data have been collected from Na(2)MoO(4) and Na(2)WO(4) to a resolution of sin (θ)/λ = 1.25 Å(−1), which is substantially better than the previous analyses using Mo Kα X-rays, providing roughly triple the number of measured reflections with respect to the previous studies [Okada et al. (1974 ▸). Acta Cryst. B30, 1872–1873; Bramnik & Ehrenberg (2004 ▸). Z. Anorg. Allg. Chem. 630, 1336–1341]. The unit-cell parameters are in excellent agreement with literature data [Swanson et al. (1962 ▸). NBS Monograph No. 25, sect. 1, pp. 46–47] and the structural parameters for the molybdate agree very well with those of Bramnik & Ehrenberg (2004 ▸). However, the tungstate structure refinement of Okada et al. (1974 ▸) stands apart as being conspicuously inaccurate, giving significantly longer W—O distances, 1.819 (8) Å, and shorter Na—O distances, 2.378 (8) Å, than are reported here or in other simple tungstates. As such, this work represents an order-of-magnitude improvement in precision for sodium molybdate and an equally substantial improvement in both accuracy and precision for sodium tungstate. Both compounds adopt the spinel structure type. The Na(+) ions have site symmetry .-3m and are in octahedral coordination while the transition metal atoms have site symmetry -43m and are in tetrahedral coordination.